Integrated in silico and in vitro exploration of the anti-VEGFR-2 activities of a semisynthetic xanthine alkaloid inhibiting breast cancer - Eslam B. Elkaeed; Hazem Elkady; Ahmed M. Khattab; Reda G. Yousef; Hanan A. Al-ghulikah; Dalal Z. Husein; Ibrahim M. Ibrahim; Mohamed A. Elkady; Ahmed M. Metwaly; Ibrahim H. Eissa (PLoS ONE, 2025)
This study presents T-1-NBAB, a new compound derived from the natural xanthine alkaloid theobromine, aimed at inhibiting VEGFR-2, a crucial protein in angiogenesis. T-1-NBAB’s potential to interacts with and inhibit the VEGFR-2 was indicated using in silico techniques like molecular docking, MD simulations, MM-GBSA, PLIP, essential dynamics, and bi-dimensional projection experiments. DFT experiments was utilized also to study the structural and electrostatic properties of T-1-NBAB. Computational analysis was performed to predict the ADME-Tox profiles of T-1-NBAB. After semisynthesis, the in vitro results showed that T-1-NBAB effectively inhibits VEGFR-2, with an IC50 of 0.115 μM, compared to sorafenib’s 0.0591 μM. In vitro tests also demonstrated significant activity of T-1-NBAB against breast cancer cell lines MCF7 and T47D, with IC50 values of 16.88 μM and 61.17 μM, respectively, and high selectivity. Importantly, T-1-NBAB induced early and late apoptosis in MCF7 cells, indicating its potential as a strong anticancer agent. Additionally, T-1-NBAB reduced the migration and healing abilities of MCF7 cells, suggesting it could be a promising anti-angiogenic agent. Overall, these findings suggest that T-1-NBAB is a promising lead compound for further research as a potential treatment for breast cancer.